Análise da interação comunicativa na rotina entre família e jovens com Deficiência Intelectual e/ou Autismo - Silva, Francelen Larissa (2024)
The family plays a fundamental role in the development of language and communicative and social processes of their children with Intellectual Disability (ID) and/or Autism Spectrum Disorder (ASD). The general aim of this study was to analyze the use of the Evaluation Scale for Oral Language Teaching in the Family Context (EVALOF) in the context of young people. A specific objective was set to relate the family routines of young people with ID and/or ASD to the strategies used by mothers in communicative interaction, via EVALOF. Eight young people with ID and/or ASD aged between 13 and 23 and their families, represented by seven mothers and one sister, took part in the study. Two instruments were used to collect the data: Family Routine Based Interview and EVALOF. The study analyzed: 1) Qualities and difficulties of young people from the mothers' and sister's perspectives; 2) Social interaction and life in the community; 3) Family routines and satisfaction and 4) Communicative interactions and family support, via EVALOF. The analysis of the EVALOF applied to young people guided structural changes to the instrument, such as adaptations to the glossary according to the age group. The results showed that, although all the families offer some natural support to facilitate young people's communication, especially in the organization of the environment, there is a lack of specific strategies to improve communication skills. The strategies used by families were: organizing the environment, adapting the physical context, facilitating attention to young people, encouraging young people to participate in communicative interactions, responding to interactions initiated by young people, supporting them in obtaining information, expanding young people's utterances and teaching communicative skills. The study highlighted the importance of family strategies and the need to strengthen the teaching of specific communication skills to improve the interaction and oral language development of young people with ID and/or ASD.